Supply of medicines: paternalism, autonomy and reality. Issue 2 (April 1998) - Prayle, D; Brazier, M
Abstract : Radical changes are taking place in the United Kingdom in relation to the classification of, and access to, medicines. More and more medicines are being made available over the counter both in local pharmacies and in supermarkets. The provision of more open access to medicines may be hailed as a triumph for patient autonomy. This paper examines whether such a claim is real or illusory. It explores the ethical and legal implications of deregulating medicines. Do patients benefit? What is the impact on pharmacists? Are the true beneficiaries of change largely the pharmaceutical industries?